2016
DOI: 10.1002/lary.26465
|View full text |Cite
|
Sign up to set email alerts
|

Voice disorders and associated risk markers among young adults in the United States

Abstract: Objective To examine the prevalence of voice disorders in young adults and identify socio-demographic factors, health conditions, and behaviors associated with voice disorder prevalence. Study Design Cross-sectional analysis of data from the National Longitudinal Study of Adolescent to Adult Health Methods During home interviews, 14,794 young adults, aged 24–34 years, reported their health conditions and behaviors. Presence and duration of voice disorders were reported over the past 12 months. We computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 41 publications
3
39
0
6
Order By: Relevance
“…Gender has been well‐established as a risk factor for voice disorders. Previous studies have demonstrated that women have a higher prevalence of voice disorders compared to males . The differences in laryngeal anatomy and phonatory physiology in women may contribute to a higher frequency of reported voice disorders .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Gender has been well‐established as a risk factor for voice disorders. Previous studies have demonstrated that women have a higher prevalence of voice disorders compared to males . The differences in laryngeal anatomy and phonatory physiology in women may contribute to a higher frequency of reported voice disorders .…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we are the first to report health disparities and barriers in access to care in a national study of adults who reported voice problems in the United States. There have been relatively few epidemiological studies investigating disparities or healthcare access among adults with voice disorders . The annual prevalence of voice problems among adults in the United States has been reported to be 6% to 8% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure illustrates the process involved for article screening and selection using the Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) statement. Five studies were found to be suitable for inclusion. The study characteristics in terms of study design and participant details are depicted in Table .…”
Section: Resultsmentioning
confidence: 99%
“…All the studies mentioned taking informed consent from the participants, except Wang et al . The sample size and drop‐ out rate justification was provided only by one study . The GRADE approach rated all studies as a low rating, since all used an observational study design.…”
Section: Resultsmentioning
confidence: 99%